Antibody‐Based CAR T Cells Produced by Lentiviral Transduction. (4th March 2020) - Prommersberger, Sabrina; Hudecek, Michael; Nerreter, Thomas
Abstract: One promising approach to treat hematologic malignancies is the usage of patient‐derived CAR T cells. There are continuous efforts to improve the function of these cells, to optimize their receptor, and to use them for the treatment of additional types of cancer and especially solid tumors. In this protocol, an easy and reliable approach for CAR T cell generation is described. T cells are first isolated from peripheral blood (here: leukoreduction system chambers) and afterwards activated for one day with anti‐CD3/CD28 Dynabeads. The gene transfer is performed by lentiviral transduction and gene transfer rate can be verified by flowcytometric analysis. Six days after transduction, the stimulatory Dynabeads are removed. T cells are cultured in interleukin‐2 conditioned medium for several days for expansion. There is an option to expand CAR T cells further by co‐incubation with irradiated, antigen‐expressing feeder cell lines. The CAR T cells are ready to use after 10 (without feeder cell expansion) to 24 days (with feeder cell expansion). © 2020 The Authors. Basic Protocol : Generation of CAR T cells by lentiviral transduction